2015
DOI: 10.15407/fz61.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning versus intermittent hypoxia training: a comparative analysis for cardioprotection

Abstract: Ischemic preconditioning (IPC) is an adaptive phenomenon that occurs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…96,97,100,193,194 Further information on the cardioprotective effects of IHT are available in the recent reviews by Zhang and Zhou 195 and by Serebrovska and Shatilo. 196 Various antistress effects of IHT have been described by IHT pioneer Felix Meerson. 179 He and his co-workers found that IHT prevented stomach ulcers induced by restraint stress and behavioral disorders in rats.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
“…96,97,100,193,194 Further information on the cardioprotective effects of IHT are available in the recent reviews by Zhang and Zhou 195 and by Serebrovska and Shatilo. 196 Various antistress effects of IHT have been described by IHT pioneer Felix Meerson. 179 He and his co-workers found that IHT prevented stomach ulcers induced by restraint stress and behavioral disorders in rats.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
“…Hypoxic preconditioning (HPC) or ischemic preconditioning (IPC) can improve the tolerance of cells, tissues, entire organs, and even the organism itself to subsequent severe hypoxia or ischemia [68]. The phenomenon of preconditioning has been observed in various studies [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Remote ischemic preconditioning (RIPC) is a nonpharmacological therapeutic strategy to protect vascular function through intermittent ischemia. RIPC initiates alternate and intermittent episodes of ischemia by cutting off blood flow to nontarget tissue (often the arms or legs) [26]. Moreover, numerous clinical trials have already supported RIPC's anti-ischemic protective effects on the heart, brain, and other important organs [27][28][29].…”
Section: Introductionmentioning
confidence: 99%